Determinan tata kelola pemerintahan pada OPD kabupaten Bima - Nadia Ersy Mithasarinama; Biana Adha Inapty; Nurabiah (Akuntansi dan Teknologi Informasi, 2023)
This study aims to examine whether the regional financial accounting system, human resource competence, transparency and accountability of financial management have an effect on good governance. The approach used is quantitative data. This study’s population is all OPD in Bima Regency with the sample criteria, namely employees who carry out accounting or financial administration functions. The sampling technique used was purposive sampling with a sample of 122 respondents. The results of this study indicate that regional financial accounting systems and financial management transparency have no effect on good governance, while human resource competency and financial management accountability have a positive effect on good governance. The implication of this research is that the Bima Regency Government can improve the competence of employees who work as financial managers by providing education and training related to good governance and placing appropriate apparatus in the field of regional financial management. The results of the research contribute to enriching knowledge regarding the application of Stewardship Theory. The government as the holder of the trust can carry out good governance. The financial accounting system must comply with predetermined standards so it can produce financial reports that can be accounted for, are relevant, reliable, comparative and verifiable.